2011
DOI: 10.1055/s-0031-1295686
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Colorectal Cancer

Abstract: Obesity is a risk factor for colorectal cancer based on its molecular and metabolic effects on insulin and IGF-1, leptin, adipocytokines, and sex hormones. Obese men have a higher risk of colorectal cancer compared with normal weight men, but the association between obesity and rectal cancer is weaker than with colon cancer. There is a weaker association between obesity and colon cancer in women than in men, and no appreciable association between obesity and rectal cancer in women. Although obesity does not se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 72 publications
0
36
1
Order By: Relevance
“…Daily inactivity can increase the incidence of obesity, which is another risk factor for CRC (Bardou et al, 2013). The precise mechanism of the protective effect of physical activity is still unclear, but it seems that physical activity lowers the risk of CRC by reducing BMI, reducing the colonic transit time, and lowering insulin levels (Gribovskaja-Rupp et al, 2011;Mao et al, 2003). Obesity increases serum leptin levels (Frezza et al, 2006); leptin leads to CRC development (Sierra-Honigmann et al, 1998).…”
Section: Physical Activity and Obesitymentioning
confidence: 99%
“…Daily inactivity can increase the incidence of obesity, which is another risk factor for CRC (Bardou et al, 2013). The precise mechanism of the protective effect of physical activity is still unclear, but it seems that physical activity lowers the risk of CRC by reducing BMI, reducing the colonic transit time, and lowering insulin levels (Gribovskaja-Rupp et al, 2011;Mao et al, 2003). Obesity increases serum leptin levels (Frezza et al, 2006); leptin leads to CRC development (Sierra-Honigmann et al, 1998).…”
Section: Physical Activity and Obesitymentioning
confidence: 99%
“…Excessive fat accumulation, including overweight and obesity, defined as a body mass index (BMI) of 25-29.9 and C30 kg/m 2 , respectively, according to the World Health Organization (WHO), has emerged as an important lifestyle-related factor for the development of CRC [7,8]. The relationship between obesity and CRC incidence has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is no conclusive evidence that obesity predisposes to poorer survival in CRC patients [6,8,9]. For example, a US cohort study of 2,303 non-metastatic CRC patients showed that pre-diagnostic obesity was significantly associated with an increased risk of death resulting from all causes and from CRC [11].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin and insulin-like growth factor 1 together can promote CRC by activating several signalling pathways associated with an elevated risk of oncogenesis. 32 That insulin may play a role in the development of CRC is supported by the association between type 2 diabetes and an elevated risk of cancer including CRC. 33,34 Since the Mediterranean and DASH diets are very similar (e.g.…”
Section: Health Promotion and Chronic Disease Prevention In Canadamentioning
confidence: 99%